(untitled) (Mustansiria Dental Journal, 2018)
Background: some properties of heat-cured acrylic resin are required to be improved (like flexural strength, hardness and porosity) by adding different types of fibers like polypropylene fiber, also needed to determine these properties with addition of polypropylene fibers and curing the polymer by autoclave. The aim of this study was to evaluate the effect of adding polypropylene fibers in two different lengths (6mm, 12mm) and concentration 2%, and the effect of autoclave processing on some properties(flexural, surface hardness and porosity). Material and method: A total No. of 120 specimens were prepared in this study and divided into two main groups according to length of fibers (6mm,12mm) , each main group was subdivided into two groups according to method of adding the fiber (directly to the powder or immersed in monomer). Each group of them contain 10 specimens for each test. Result: in this study, the transverse strength and surface hardness of heat cured acrylic reinforced by randomly oriented polypropylene fibers (12mm, 2%) regardless to application method with higher significance than other groups. Fiber reinforcement and autoclave processing showed non-significant effect on porosity of heat cure acrylic resin according to ANOVA t-test. Conclusion: Reinforcement by randomly oriented polypropylene fiber (12mm, 2%) added with and without immersion in monomer better than other groups according to transverse strength and surface hardness with autoclave processing but there is no effect of added fibers on porosity test.